Prevalence of peripheral arterial disease in patients with diabetes mellitus in a primary care setting - Rabia, K.; Khoo, Ee Ming (Malaysian Medical Association, 2007)
The aims of the study were to determine the prevalence of peripheral arterial disease (PAD) in diabetic patients and in different ethnic groups at a primary care setting, and to evaluate risk factors associated with PAD in these diabetic patients. A cross sectional study of 200 diabetic patients over 18 years old who attended a primary care clinic at a teaching hospital in Kuala Lumpur, Malaysia was carried out. Face-to-face interviews were conducted using structured questionnaires for demographic characteristics and risk factors evaluation. Blood pressure measurements, assessment of peripheral neuropathy and ankle brachial pressures were performed. PAD was diagnosed by an ankle brachial pressure index (ABPI) of <0.9 on either leg. The overall prevalence of PAD was 16 in this diabetic population. The prevalence of PAD was 5.8 in Malays, 19.4 in Chinese and 19.8 in Indians. The prevalence of peripheral neuropathy was 41, foot ulcer 9.5, and gangrene 3.0. The presence of foot ulcer was weakly associated with PAD (P=0.052). No significant relationships were found between age, gender, smoking status, duration of diabetes mellitus, hypertension, dyslipidaemia, and PAD. PAD is common in the diabetic population of this study.